Haemangioma left pinna with extensive, multiple skin ulcerations - Rabbani, SM Golam; Chowdhury, M Alamgir; Yasmeen, Naseem; Malakar, Mousumi (Bangladesh Journal of Otorhinolaryngology, 2010)
Hemangioma is a benign vascular tumours constitute 7% of all benign tumours arise from arterioles, venules & capillaries. It is deep red or blue-purple in colour, blench on pressure. Usually it is small & of no consequence is seen in isolation, but few may be multiple and /or part of a wider syndrome. It is prone to extenssive bleeding if wall is damaged. It is best treated with cryosungery or laser or if so large then by ligation or embolization of the feeding vessels. Here we have encountered a case of haemangioma in the left pinna with extensive and multiple ulcerations of the skin, which is not so common site for development. Key words: Hemangioma; pinna. DOI: 10.3329/bjo.v16i1.5785 Bangladesh J Otorhinolaryngol 2010; 16(1): 70-72